Frieze Art Fair : Yearbook 2008-9. - Arcangel, Cory; Büchler, Pavel; Floyer, Ceal; Greenfort, Tue; Hayes, Sharon; Hein, Jeppe; Jeane, Norma; Kurant, Agnieszka; Prieto, Wilfredo; Rodriguez, Bert; Ruppersberg, Allen; Slominski, Andreas; et al. (London : Frieze London, 2009)
Arcangel, Cory ; Büchler, Pavel ; Floyer, Ceal ; Greenfort, Tue ; Hayes, Sharon ; Hein, Jeppe ; Jeane, Norma ; Kurant, Agnieszka ; Rodriguez, Bert ; Ruppersberg, Allen ; Slominski, Andreas ; Prieto, Wilfredo ; Abdessemed, Adel ; Ahtila, Eija-Liisa ; Alimpiev, Victor ; Arad, Ron ; Arakawa, Ei ; Araki, Nobuyoshi ; Araoz, Nicanor ; Argianas, Athanasios ; Auerbach, Tauba ; Avery, Charles ; Bader, Darren ; de Balincourt, Jules ; Balka, Miroslaw ; Bartana, Yael ; Bartuszová, Mária ; Bas, Hernan ; Bell, Dirk ; Berkenblit, Ellen ; Bessone, Amy ; Bickerton, Ashley ; Blightman, Juliette ; Bodzianowski, Cezary ; Bohl, Henning ; Böhnisch, Peter ; Bozkurt, Osman ; Bradley, Joe ; Brandenburg, Ulla von ; Bratkov, Sergey ; Brungs, Bernhard ; Bryans, Matt ; Budny, Michal ; Bulatov, Erik ; Buldakov, Alex ; Burr, Tom ; Butzer, André ; Cahn, Miriam ; Carter ; Casebere, James ; Channer, Alice ; Cinto, Sandra ; Claerbout, David ; Clements, Neil ; De Cock, Jan ; Condo, George ; Conrad, Tony ; Cuoghi, Vanni ; Dadson, Andrew ; Dardot, Marilá ; Davenport, Ian ; Dean, Tacita ; Dedobbeleer, Koenraad ; Deller, Jeremy ; Detanico, Angela ; Lain, Rafael ; diCorcia, Philip-Lorca ; Djurberg, Nathalie ; Doherty, Willie ; Donnelly, Trisha ; Dumas, Charlotte ; Duwenhögger, Lukas ; Echeverri Fernandez, Tatiana ; Egan, Aleana ; Eichwald, Michaela ; Elmgreen, Michael ; Dragset, Ingar ; Eloyan, Armen ; Engh, Marius ; Erkmen, Ayse ; de Espirito Santo, Iran ; Ethridge, Roe ; Fairhurst, Angus ; Feldmann, Hans-Peter ; Ferreira, Angela ; Ferris, Dee ; Finch, Spencer ; Fisher, Morgan ; Fogarasi, Andreas ; Förg, Gunther ; FOS ; Freymann, Alejandro ; Friedl, Peter ; Frost, Alistair ; Gabbiani, Francesca ; Gabellone, Giuseppe ; Gabriel, Ingeborg ; Gall, Neil ; Garcia, Carmela ; Gmelin, Felix ; Godinat, Aloïs ; etc.
Frieze Art Fair 200, Frieze, London, 2008-10-16. 2008-10-19
boek